Measuring behaviour an introductory guide - Martin, Paul 1958 May 11- (Cambridge University Press, 1995)
Measuring Behaviour is a guide to the principles and methods of quantitative studies of behaviour, with an emphasis on techniques of direct observation, recording and analysis. In this new edition, all sections have been updated and revised, some have been expanded and others introduced for the first time. Aimed primarily at undergraduate and graduate students in biology and psychology who are about to embark upon behavioural research projects, this book provides a concise review of methodology that will also be of interest to scientists of all disciplines in which behaviour is measured. Written with brevity and clarity, it is intended, above all, as a practical guide book.